2017
DOI: 10.1186/s40538-016-0083-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promotion using microbial IAA producers in conjunction with azolla: a novel approach

Abstract: Studies were conducted to find efficient Indole acetic acid producing strains and assessing the effectiveness of combined dose of azolla (dried) and IAA producers on plant growth. Out of ten isolates, only two isolates, viz, F1 and G2 were found to be potent IAA producers and were used for further experiments. It was found that the isolate F1 and G2 produced maximum amount of IAA at 0.9% tryptophan and incubation for 72 h at room temperature. The optimum pH for IAA production for isolates F1 and G2 was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 19 publications
5
18
0
1
Order By: Relevance
“…produced more IAA at pH 9, but this production decreased with the pH decrease. Similarly, previous studies showed that the maximum yield of IAA was obtained at pH 9 [14,45]. Other authors found that the maximum amount of IAA was produced at neutral to slightly alkaline pH [37,46,47].…”
Section: Discussionsupporting
confidence: 56%
“…produced more IAA at pH 9, but this production decreased with the pH decrease. Similarly, previous studies showed that the maximum yield of IAA was obtained at pH 9 [14,45]. Other authors found that the maximum amount of IAA was produced at neutral to slightly alkaline pH [37,46,47].…”
Section: Discussionsupporting
confidence: 56%
“…Earlier reports have shown that plant-associated bacteria can improve plant growth by IAA production [10,[21][22][23] and nitrogen fixation [8]. In this study, bacterial inoculation also showed positive effects on the growth of sweet potato.…”
Section: Discussionsupporting
confidence: 69%
“…The highest level, 78.7 µg/mL, was produced by isolate Bacillus pumilus followed by Bacillus subtilis (72.0 µg/mL) when the media was supplemented with 500 µg/mL of l -tryptophan. It was investigated that IAA is the most important plant hormone produced by rhizobacterial strains which is directly involved in plant growth promotion [15]. The production of siderophores, low molecular weight iron chelating compounds, was detected in both isolates, conferring them a competitive merit to biocontrol agents.…”
Section: Resultsmentioning
confidence: 99%